2022
DOI: 10.1186/s12889-022-13221-w
|View full text |Cite
|
Sign up to set email alerts
|

The burden of aortic aneurysm in China from 1990 to 2019: findings from the Global Burden of Disease Study 2019

Abstract: Background Aortic aneurysm (AA) is a global public health concern. However, little is known about the disease burden of AA in China. Methods Following the general analytic strategy used in the Global Burden of Disease Study (GBD) 2019, we analyzed the mortality and years of life lost (YLLs) due to AA, stratified by sex, age, and province-level region in China from 1990 to 2019. The temporal trend of AA burden in China was analyzed and the main attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
(48 reference statements)
1
2
0
Order By: Relevance
“…Implementation of automated external defibrillator outside hospital settings in China is minimal and must be strengthened. Consistent with a previous study [8] , we found increasing ASMR of AA from 2013 to 2020, which in turn may be attributed to increased metabolic risk factors, such as high blood pressure and atherosclerosis [24,25] , and improved diagnostic standards and screening technology [26] . In sharp contrast to the Global downward trend [27,28] , we found a slight increase in the ASMR of NRVHDs in recent years, suggesting insufficient programs for diseases with low but increasing ASMR.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Implementation of automated external defibrillator outside hospital settings in China is minimal and must be strengthened. Consistent with a previous study [8] , we found increasing ASMR of AA from 2013 to 2020, which in turn may be attributed to increased metabolic risk factors, such as high blood pressure and atherosclerosis [24,25] , and improved diagnostic standards and screening technology [26] . In sharp contrast to the Global downward trend [27,28] , we found a slight increase in the ASMR of NRVHDs in recent years, suggesting insufficient programs for diseases with low but increasing ASMR.…”
Section: Discussionsupporting
confidence: 90%
“…The increase in the ASMR of heart diseases during the study period in Xinjiang is perplexing and may involve increased exposure to risk factors and lifestyle issues. Higher ASMR is associated with lower sociodemographic index [25] . We also noticed decreased standard deviation of ASMR of heart diseases in and number of provinces during the study period, indicating narrowing regional disparity.…”
Section: Discussionmentioning
confidence: 99%
“…[2] According to the Global Burden of Disease 2019 findings, aging populations in industrialized countries are living longer but in poorer health, and healthcare systems are heavily burdened. [3] Presently, the global population is witnessing a shift toward an unprecedented era of population aging. Recent data reveals that approximately 9% of the world’s populace has surpassed the age of 65, and this proportion is projected to escalate to 16% by 2050.…”
Section: Introductionmentioning
confidence: 99%